Exposure to dissolved TNT causes multilevel biological effects in Baltic mussels (Mytilus spp.). (May 2021) - Schuster, Romina; Strehse, Jennifer S.; Ahvo, Aino; Turja, Raisa; Maser, Edmund; Bickmeyer, Ulf; Lehtonen, Kari K.; Brenner, Matthias
Abstract: Baltic mussels ( Mytilus spp.) were exposed to the explosive trinitrotoluene (TNT) for 96 h (0.31–10.0 mg/L) and 21 d (0.31–2.5 mg/L). Bioaccumulation of TNT and its degradation products (2- and 4-ADNT) as well as biological effects ranging from the gene and cellular levels to behaviour were investigated. Although no mortality occurred in the concentration range tested, uptake and metabolism of TNT and responses in antioxidant enzymes and histochemical biomarkers were observed already at the lowest concentrations. The characteristic shell closure behaviour of bivalves at trigger concentrations led to complex exposure patterns and non-linear responses to the exposure concentrations. Conclusively, exposure to TNT exerts biomarker reponses in mussels already at 0.31 mg/L while effects are recorded also after a prolonged exposure although no mortality occurs. Finally, more attention should be paid on shell closure of bivalves in exposure studies since it plays a marked role in definining toxicity threshold levels. Highlights: Shell closing as simple defence against acute toxicity of TNT. Mussels appear to be able to metabolize TNT to 2- and 4-ADNT.Biomarker responses occurred already at the lowest TNT exposure concentrations. Biomarker responses occurred already at the lowest TNT exposure concentrations.